Dacryo Cysto Rhinostomy with Intubation: Anterior Flap Versus Flap Excision. A Comparative Study - Memon, Mariya Nazish; Sheikh, Sajida Parveen; Sheikh, Waheed Ahmed; Memon, Farah Naz; Narsani, Ashok Kumar (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objective: To assess the efficacy of dacryocystorhinostomy with intubation, with and without anterior flap suturing in patients with chronic dacryocystitis secondary to the nasolacrimal duct obstruction. Methodology: Comparative cross-sectional study was carried out at Institute of Ophthalmology, Liaquat University of Medical & Health Sciences Jamshoro. All the patients underwent external dacryocystorhinostomy during July 2016 to June 2019 were included by convenient sampling technique. Patient’s data were allocated into two groups. Group A (Anterior flap anastomosis) and group B (flap excision). Success rate of surgery was assessed at 3 months and 6 months follow up visits. Data were analysed by SPSS 23, frequencies and percentages for categorical variables and mean and averages for numerical variables were calculated, x2 (chi- square) applied on surgical outcome comparing two techniques. P-value< 0r = 0.05 was considered as significant. Results: Fifty-seven patients (57 eyes) were included in this study. Thirty-four eyes in Group A (anterior flap suturing) and 23 eyes in Group B (flap excision). Mean age of the patient in Group A was 42.50 years±11.88 and in Group B was 42.10 years±16.78 (P-0.923). Most of the operated patients were females such as 55.9% and 69.6% in Group A and B respectively (P-0.298). The overall success outcome of DCR with silicon tube intubation was 93%. Thirty-one eyes (91.2%) in Group A and 22 eyes (95.7%) in Group B were labelled as successful (P–0.641). Conclusion: Excision of mucosal flap is effective and comparatively easier. It shortens the procedure time and decrease hazards of general anaesthesia. Key Words: Chronic Dacryocystitis, dacryocystorhinostomy, Epiphora, Flap anastomosis, Flap excision.